The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1182/blood.v76.2.368.bloodjournal762368
|View full text |Cite
|
Sign up to set email alerts
|

Expression of platelet glycoprotein Ib by cultured human megakaryocytes: ultrastructural localization and biosynthesis

Abstract: Glycoprotein Ib (GPIb), the receptor for von Willebrand factor, is a two-chain member constituent of the platelet/megakaryocytic lineage. Studies on its expression have been hampered by the difficulties in obtaining purified megakaryocytes in a sufficient number. We report a suspension liquid culture procedure that allowed isolation of more than 1 x 10(6) megakaryocytes with a purity ranging from 3% to 88% from the blood of patients with chronic myeloid leukemia, from fetal liver or from normal human bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A significant reduction of YAP was observed in YAP-knockdown cells, and reduction of both YAP and TAZ was observed when a plasmid targeting both YAP and TAZ (shYAP/TAZ) was introduced into these cells ( Figure 1 A,B). CD41, which is a common marker for megakaryocyte and platelets, is expressed on the plasma membrane of mature megakaryocyte cells prior to platelet release [ 10 , 11 ]. Our previous work and other studies demonstrated that 20–40% of a population of MEG-01 cells is made up of CD41 + cells, and MEG-01 cells can produce platelet-like particles (PLPs) either spontaneously or upon treatment with platelet induction agents, such as valproic acid (VPA) [ 4 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…A significant reduction of YAP was observed in YAP-knockdown cells, and reduction of both YAP and TAZ was observed when a plasmid targeting both YAP and TAZ (shYAP/TAZ) was introduced into these cells ( Figure 1 A,B). CD41, which is a common marker for megakaryocyte and platelets, is expressed on the plasma membrane of mature megakaryocyte cells prior to platelet release [ 10 , 11 ]. Our previous work and other studies demonstrated that 20–40% of a population of MEG-01 cells is made up of CD41 + cells, and MEG-01 cells can produce platelet-like particles (PLPs) either spontaneously or upon treatment with platelet induction agents, such as valproic acid (VPA) [ 4 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…This receptor is normally expressed on the platelet plasma membrane at an average copy number of 25,000 per platelet. During thrombopoiesis GPIb is expressed as early as the megakaryoblast (4). Under normal physiologic conditions, resting platelets do not adhere to each other or to leukocytes and endothelial cells (5).…”
Section: Introductionmentioning
confidence: 99%
“…Upon stimulation with platelet agonists, megakaryocytes aggregate and start secretion, which is accompanied by Ca2+ oscillations [14]. Their plasma membrane has the same proportion of phospholipids and fatty acids [15, 161 and contains glycoproteins IbIIX [17] and a,,,P, [18, 191. The results reveal heterogeneity in P3 mobility both in resting megakaryocytes and during stimulation.…”
Section: Introductionmentioning
confidence: 99%